factors related to utilization of antenatal care in Nepal: A generalized linear approach - Shrestha, Gauri (Journal of Kathmandu Medical College, 2014)
Background: Antenatal care provides an entry point for pregnant women to the health care system. Proper utilization of available health services essential for successful implementation of health programmes. Objectives: This study investigates factors associated with the use of maternal health services in terms of number of antenatal care visits. Methods: For analyzing the use of antenatal care health services in Nepal, data was extracted from individual recodes of a data file of Nepal Demographic Health Survey 2006. The unit of analysis for this study was Ever Married Woman (who had at least one live birth in the five years preceding the survey). The sample of study consisted of 4182 Ever Married Woman. The response variable has numbers as its possible outcome therefore generalized Poisson regression model was selected for establishing linkage between number of antenatal care visits and several explanatory variables. Results: The result of this study shows that women with low education level, those residing in rural areas and those with low socio-economic status are less likely to attend antenatal care visits. Conclusion: This study confirms that antenatal care visit is indeed an effective entry point for delivery care. Programmes directed at improving and increasing the accessibility of antenatal care are important to improve maternal health, especially in developing countries like Nepal. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10629 Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, Page: 69-74